Diseño de una herramienta para el uso de indicadores en procesos de Evaluación de Impacto Ambiental - Campos-Vargas, Emmanuel (Instituto Tecnológico de Costa Rica, 2015)
An environmental indicator is defined as a variable that provides key information on environmental conditions and the effects of human development. In Costa Rica, these indicators must be submitted for projects that require an environmental management plan in order to complete an EIA process. However, there is no law or validated literature by the National Environmental Technical Secretariat that indicate criterion to follow for a successful indicator construction. Furthermore the institution has encountered problems such as subjectivity, inaccuracy and inadequate traceability in environmental indicators reviewed. This research propose a tool that allows the construction, evaluation, selection and monitoring of environmental indicators in environmental management plans (EMP). This study involves the application of interviews to institutions responsible EIA process in Colombia and Switzerland, using the Delphi method and visits to projects in environmental regency as a primary source of information. The main results of this research are: "Manual for the construction, evaluation and selection of environmental indicators in Environmental Management Plans" and "Procedure for environmental monitoring and use of indicators in constructions"; both products were applied to real projects. During the implementation of the manual greater number of environmental indicators with better conceptual bases were achieved in comparison to a previous EMP. Moreover, during the application of the procedure it was possible to obtain an assessment of compliance with environmental commitments by calculating the environmental performance.
Proyecto de Graduación (Licenciatura en Ingeniería Ambiental) Instituto Tecnológico de Costa Rica, Escuela de Química, 2015.
Keywords: Indicadores; SETENA; Gestión ambiental; Impacto ambiental; Desempeño ambiental